Creation of a Nursing Intervention Model to Support Decision Making by Elderly Advanced Cancer Patients and Their Families About the Place of Death, and Evaluation of the Model's Appropriateness and Clinical Applicability. Issue 6 (December 2021) - Minamiguchi, Yoko; Suzuki, Kumi
Abstract : Elderly patients with advanced cancer and their families need to be supported in the process of making a decision about a place to die. The objective of this research was to evaluate the appropriateness and clinical applicability of a nursing intervention model we developed to support decision making by elderly advanced cancer patients and their families about the place of death. We created the Nursing Intervention Model using the framework of the nursing intervention model reported by McEvoy and Egan (1979). Our survey was performed on 5 physicians and 9 nurses engaged in decision making about the place of terminal care and death for cancer patients. Focus group interviews were conducted to determine the appropriateness of the model. A content analysis technique was used to analyze the data obtained. Survey participants expressed an overall view that the contents of "Intervention Focus" and "Nursing Activity" are generally appropriate. On the other hand, the challenges to be addressed include clarification of which patients the model is applicable to support their decision making, positioning within the model of factors that influence the decision-making process, and further identification of the roles of nurses in an interdisciplinary approach to health care.